Hama Infasif Ulat Grayak Spodoptera frugiperda (J.E. Smith) pada Tanaman Jagung di Kabupaten Minahasa - Juliet M. Eva Mamahit; Jusuf Manueke; Sandra E. Pakasi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Mamahit JME, Manueke J, Pakasi SE. 2020. Infasive pests fall army worm spodoptera frugiperda (J.E. Smith) on maize in minahasa district. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The fall army worm Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) is an invasive pest attacking maize plants in various regions in Indonesia. This pest is a very damaging pest of maize that originates from America and entered Indonesia on 2019 in the Sumatra region. The fall army worm attack was reported in 13 provinces in Indonesia, including North Sulawesi. This study aims to observe the presence of fall army worm in several maize plantations in the maize production centers area, namely in Minahasa Regency, North Sulawesi Province, and to determine the intencity and damage of attack caused by S. frugiperda on maize plants. This study used a survey method with purposive sampling, to determine the location of maize plantations that were attacked by S. frugiperda. Furthermore, in the field, the symptoms of attack were observed and the incidence of attacks was calculated based on the presence or absence of attack symptoms, and calculated the level intensity of S. frugiperda pest attack. The results showed that S. frugiperda has distributed in several maize plantations in Minahasa Regency, namely: in Langowan Utara, Langowan Timur, Langowan Barat, Langowan Selatan, Tompaso, Kakas and Remboken, with the intensity of attacks level from low until severe. The attack percentage of S. frugiperda from 30% to 70%.